2010
DOI: 10.5771/0949-6181-2010-3-207
|View full text |Cite
|
Sign up to set email alerts
|

Factors of effective strategy implementation: Empirical evidence from Slovenian business practice

Abstract: Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden. Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen. Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in der dort genannten Lizenz … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(79 citation statements)
references
References 54 publications
2
52
0
2
Order By: Relevance
“…Earlier studies in emerging markets have provided a certain amount of information about strategic choice and strategy implementation (Brenes, et al, 2008;Parnell, 2008;Glaister et al, 2009;Parnell, 2009;Čater and Pučko, 2010;Aldehayyat and Anchor, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies in emerging markets have provided a certain amount of information about strategic choice and strategy implementation (Brenes, et al, 2008;Parnell, 2008;Glaister et al, 2009;Parnell, 2009;Čater and Pučko, 2010;Aldehayyat and Anchor, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, what is most important here to note is that strategy owners should focus on both objective risk factors as well as perceived risk that stem from subjective evaluation of attributes defining the implementation environment. Strong (though indirect) empirical support for this hypothesis is the fact that lack of communication is listed in numerous studies that looked at strategy implementation problems (Al-Ghamdi, 1998;Alexander, 1985;Čater & Pučko, 2010;Hambrick & Cannella, 1989;Heide, Grønhaug, & Johannessen, 2002;Hrebiniak, 2006). Communication is the most important tool to remove what in financial theory is called unsystematic risk, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the practical relevance of above results, a recent study on obstacles to strategy implementation for 172 Slovenian businesses (Čater & Pučko, 2010) reports the lack of adequate incentive systems as the most frequently named implementation problem by the group of companies studied. Earlier studies had also identified lack of effective rewards mechanisms as implementation problems (Al-Ghamdi, 1998;Alexander, 1985) or have highlighted their importance for successful strategy implementation (Hrebiniak, 2006;Shah, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Cater and Pucko (2010) recommended that there was a relationship between the good organizational structure and organizational performance in Slovenia; therefore, they recommended that further studies should involve it in other sectors, such as the education sector. Rahimian, et al (2009) and Alashloo, et al, (2005), in their studies on the higher education sector in Iran, have linked between the organizational structure and organizational culture and considered them as success factors having a positive impact on the organizational performance.…”
Section: The Organizational Structure and Organizational Performancementioning
confidence: 99%
“…Studies on strategy execution (including organizational structure and organizational culture) and performance are presumed to be abundant, where several authors have significantly contributed in this area (Wilden, Gudergan, Nielsen and Lings, 2013;Alamsjah, 2011;Pucko and Cater, 2010;Mieso, 2010;Rahimnia, et al, 2009;Li, Guohui & Eppler, 2008;Hrebiniak, 2008;Neilson, Martin & Power, 2008;Malik, 2007;Malik, 2007;Higgins, 2006;Okumas, 2003). These authors (e.g.…”
Section: Introductionmentioning
confidence: 99%